FACTORS AFFECTING NURSE TURNOVER IN HOSPITAL: A LITERATURE REVIEW - Christiani, Luvi; Ilyas, Jaslis (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: A turnover occurrence in the hospital was a constant problem. The cause of turnover was largely inclined to the level of job satisfaction, hostile work environment, excessive workload, resulting in a lack of motivation to stay. Methods: This study was conducted in a narrative review by looking at the factors causing turnover at various hospitals. The review was done by searching for articles and journals related to factors that lead to nurse turnover in the hospital. The referral journals are published in the accredited journal publications. The literature investigation was conducted in October-December 2017 through Universitas Indonesia online library and Google Scholar. Journals were selected based on predefined criteria and carried out a critical appraisal process. Results: The results of the journal investigation showed that some factors that support the nurse turnover in the hospital were the poor work environment, job dissatisfaction, excessive workload, the poor relationship between nurse and manager, lack of self-appreciation, burnout and low social support. Conclusions: The suggestion that can be given is to improve the work environment that is emphasized through policies to maintain the nurse in the workplace.Â